Anti-muscarinic drugs as preventive treatment of exercise-induced bronchoconstriction (EIB) in children and adults. (October 2020) - Bonini, Matteo; Cilluffo, Giovanna; La Grutta, Stefania; Boccabella, Cristina; Usmani, Omar; Viegi, Giovanni; Palange, Paolo
Abstract: Regular physical activity is strongly recommended to prevent chronic respiratory diseases, including asthma. On the other hand, vigorous physical training may trigger airway symptoms and bronchoconstriction. The transient airway narrowing occurring because of exercise is named exercise-induced bronchoconstriction (EIB). Despite management according to guidelines, a significant proportion of patients experiences uncontrolled EIB, which thus represents a relevant unmet medical need. In particular, although prevention and treatment of EIB are effectively based on the use of beta-2 bronchodilator drugs, high heterogeneity in individual responses has been reported. Furthermore, even though beta-2 adrenergic drugs remain the mainstay of EIB management, occurrence of tolerance and side effects, as well as doping concerns have been reported with their use. In regard to this, inhaled antimuscarinics could represent an alternative or additional effective and safe bronchodilator therapeutic option for achieving optimal EIB control and minimize adverse events. The present systematic review aims to collect and provide the most updated and evidence-based literature findings on the efficacy and safety of short- and long-acting inhaled anti-muscarinic drugs for the preventive treatment of EIB in both children and adults. Take-Home Message: Anti-muscarinic drugs are effective and safe in preventing EIB, despite response variability is reported. Further studies should focus on long-acting molecules, chronic administration and phenotype-driven effects. Highlights: Anti-muscarinic drugs are effective in preventing EIB. Anti-muscarinic drugs are safe in preventing EIB. Further studies should focus on long-acting molecules and phenotype-driven effects.